NTRK Fusion Genes in Thyroid Carcinomas: Clinicopathological Characteristics and Their Impacts on Prognosis - Pekova, Barbora; Sykorova, Vlasta; Mastnikova, Karolina; Vaclavikova, Eliska; Moravcova, Jitka; Vlcek, Petr; Lastuvka, Petr; Taudy, Milos; Katra, Rami; Bavor, Petr; Kodetova, Daniela; Chovanec, Martin; et al. (Cancers, 2021)
Chromosomal rearrangements of NTRK genes are oncogenic driver mutations in thyroid cancer (TC). This study aimed to identify NTRK fusion-positive thyroid tumors and to correlate them with clinical and pathological data and determine their prognostic significance. The cohort consisted of 989 different TC samples. Based on the detected mutation, samples were triaged, and those that were positive for a BRAF, HRAS, KRAS, NRAS, RET, RET/PTC or PAX8/PPARγ mutation were excluded from further analyses. NTRK fusion gene testing was performed in 259 cases, including 126 cases using next-generation sequencing. NTRK fusion genes were detected in 57 of 846 (6.7%) papillary thyroid carcinomas and in 2 of 10 (20.0%) poorly differentiated thyroid carcinomas. A total of eight types of NTRK fusions were found, including ETV6/NTRK3, EML4/NTRK3, RBPMS/NTRK3, SQSTM1/NTRK3, TPM3/NTRK1, IRF2BP2/NTRK1, SQSTM1/NTRK1 and TPR/NTRK1.NTRK fusion-positive carcinomas were associated with the follicular growth pattern, chronic lymphocytic thyroiditis and lymph node metastases. NTRK1-rearranged carcinomas showed a higher frequency of multifocality and aggressivity than NTRK3-rearranged carcinomas. Tumor size, presence of metastases, positivity for the NTRK3 or NTRK1 fusion gene and a late mutation event (TERT or TP53 mutation) were determined as factors affecting patient prognosis. NTRK fusion genes are valuable diagnostic and prognostic markers.
Keywords: follow-up; poorly differentiated thyroid carcinoma; outcome; prognosis; NTRK; fusion gene; papillary thyroid carcinoma; clinicopathological feature